Strategi Rebranding Melalui Pemanfaatan Website Untuk Meningkatkan Citra PT Lumos Inisiatif Indonesia - Nurmaya Azizah; Asriyani Sagiyanto; Fajar Diah Astuti (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the rebranding strategy implemented by PT Lumos Inisiatif Indonesia through the utilization of the company’s official website, lumoshive.com, as an effort to enhance its corporate image. In the digital era, a website serves as one of the main representations of a company's identity, as well as a strategic communication channel to shape public perception. PT Lumos Inisiatif Indonesia redesigned the layout and content of its website as an initiative to project a more modern, professional, and relevant image for today’s audience. This research uses a descriptive qualitative approach with data collection techniques including interviews, observation, and documentation. The results show that changes in visual appearance, navigation structure, and content presentation on the new website are capable of delivering a more professional and innovative impression. The latest website presents branding elements such as color tones, logos, layout, and language style that are more consistent with the company's values and mission. This has a positive impact on the perception of external audiences, including partners and potential clients. However, challenges were also found, such as limited human resources for content management and the need for regular updates to keep the website relevant and engaging. In conclusion, utilizing the website as the primary medium in the rebranding strategy has proven to contribute to building a stronger image for PT Lumos Inisiatif Indonesia. Nevertheless, a more structured and responsive digital management strategy is still needed to achieve more optimal and sustainable results.